1957
DOI: 10.1042/bj0670540
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of carbohydrase action. 3. The action pattern of β-amylase

Abstract: di-iodotyrosine is present in higher concentration in the plasma of the immunized rabbits than in that of the normal ones. It is suggested that this is due to combination of the hapten with antibodies in the plasma of the immune animals. 3. During the same period inorganic iodide is also present in higher concentration in the plasma of the immunized rabbits than in that of the normal ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

1960
1960
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…However, the pH values in the latter study only varied between pH 5.1 and 7.6 and this range may be too small to greatly affect amylase action pattern. Bailey & Whelan (1957) also found that, at optimum pH, the level of single attack action of β-amylase decreased with increasing temperature between 0 and 20 • C, was more or less constant between 20 and 60…”
Section: Amylases Action Patternsmentioning
confidence: 95%
See 2 more Smart Citations
“…However, the pH values in the latter study only varied between pH 5.1 and 7.6 and this range may be too small to greatly affect amylase action pattern. Bailey & Whelan (1957) also found that, at optimum pH, the level of single attack action of β-amylase decreased with increasing temperature between 0 and 20 • C, was more or less constant between 20 and 60…”
Section: Amylases Action Patternsmentioning
confidence: 95%
“…Bailey & Whelan (1957) showed that with increasing pH, the action pattern of a β-amylase becomes more random. Likewise, Robyt & French (1967 reported that upon increasing the pH from the optimum pH 6.9 to 10.5 the action pattern of PPA changes from a multiple attack to a single attack action.…”
Section: Amylases Action Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzymes involved in the degradation of starch and their specific functions have been extensively reviewed (1,2,4,12,18,20,24,30). Of these enzymes, alpha and beta amylase are responsible for the bulk of the starch hydrolysis in the cereal endosperm.…”
mentioning
confidence: 99%
“…It might also be expected that polymerdegrading enzymes with a reaction mechanism intermediary between these two extremes would exist. I n a detailed study of the kinetic properties of 8-amylase) a plant enzyme that releases maltose residues from the non-reducing end of an amylose chain, such an intermediary action pattern was indeed observed in that a few maltose residues were removed at each effective enzyme-substrate encounter [5,9].In the present work, the mode of degradation of DNA and polydeoxynucleotides by mammalian DNase IV, an exonuclease that hydrolyzes doublestranded DNA from the 5'-ends [10-12], has been investigated. It is found that the enzyme does not attack its substrate in either a strictly random or in a single chain fashion.…”
mentioning
confidence: 99%